Electric current–assisted deformation behavior of Al-Mg-Si alloy under uniaxial tension. (July 2017) - Kim, Moon-Jo; Lee, Myoung-Gyu; Hariharan, Krishnaswamy; Hong, Sung-Tae; Choi, In-Suk; Kim, Daeyong; Oh, Kyu Hwan; Han, Heung Nam
Abstract: The tensile deformation behavior of Al-Mg-Si alloy under a pulsed electric current has been investigated. Specimens subjected to three types of heat treatment, solution treatment, natural aging, and artificial aging, are prepared. In solution treated specimens, elongation and flow stress increase when pulsed electric current is applied during plastic deformation; also, the Portevin–Le Chatelier (PLC) phenomenon, which is observed in the tensile test without electric current, nearly disappears when the pulsed electric current is applied. In naturally aged specimens, the flow stress decreases and the elongation significantly increases when pulsed electric current is applied during the tensile test. In artificially aged specimens, both elongation and flow stress decrease under pulsed electric current. The result of XRD analysis shows that thermal and electric current–induced annealing occurs in all specimens subjected to the electric current. Especially in the solution treated specimen, the formation of early stage precipitates from a supersaturated state might be accelerated by the electric current, in an effect distinct from Joule heating; this effect would explain the observed increase in flow stress and the disappearance of the PLC phenomenon. Microstructural observation shows that electric current accelerates the formation of microvoids around the precipitates at the grain boundary, resulting in earlier fracture in the artificially aged specimen. A constitutive model based on dislocation density model and precipitation hardening model is proposed to describe the uniaxial tensile behavior for the age hardening alloys. Based on the experimental findings, the proposed constitutive model is modified to describe the upper boundary of the ratchet shape stress-strain curve under a pulsed electric current. Thermal and electric current-induced annealing with precipitation hardening is considered simultaneously in the modified constitutive model. Phenomenological descriptions of each parameter are demonstrated considering the microstructural features observed in experiments. The modified model is capable of predicting the experimental results very well. Highlights: A tensile deformation behavior of Al-Mg-Si alloy under an electric current is investigated. Electric current can assist the annealing, aging and void formation during tension. Constitutive model to describe the non-pulsed and pulsed tensile behavior is proposed. Constitutive model is able to describe annealing and aging during pulsed tension.